Effektviserat arbetssätt för konstruktionsutvärdering - Lundmark, Emilia; Nykvist, Ida (My University, 2019)
ABSTRACT Communication will be an extremely important part of future companies. Both within the factory and the office, but also the communication between the factory and the office. In order to study this, help was taken by Plastal Industry as a company, in order to be able to answer the following questions: 1.What influences effective communication? 2. How can this be improved? To achieve this, it was chosen to start with unstructured interviews and observations around the company. Through this, the authors wanted to gain a greater understanding of the company, but also the process from idea to finished product. After that, the authors began to study a lot of literature about documents, but also a little about meetings and communication. This was later the basis of the semi-structured interviews that were to be conducted. After compiling these, it was realized that the problem was in the communication at the company. Therefore, it was decided to carry out further literature studies, since the authors wanted to further support the analysis of the company's communication. The result led to improvement suggestions for how the meeting and communication about it could be improved. However, the authors did not have the opportunity to test the result as the company did not have an ongoing project during the analysis. Because of this, the authors provided suggestions for improvement and tips on how the company can continue to work on this in the future.
Keywords: Produktion; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Production; Innovation & Entrepreneurship; Mechanical Engineering